Persentase Manfaat Media Aplikasi Kondisi Fisik untuk Atlet Bulutangkis Usia 10-12 Tahun Berbasis Smartphone Android - Titis Pambudi; Setya Rahayu; Siti Baitul Mukarromah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to determine the percentage of benefits of physical condition application media for badminton athletes aged 10-12 years based on Android smartphones. This study uses a survey-based quantitative descriptive method. The population of this study consisted of coaches at the Boyolali Regency badminton club. The sample in this study amounted to 15 coaches at the Boyolali Regency badminton club, taken using a purposive sampling technique. Data collection techniques in this study used a questionnaire instrument with a Likert scale data analysis using SPSS version 25. The results showed that the percentage of benefits of physical condition application media for badminton athletes aged 10-12 years based on android smartphones in the excellent category obtained a rate of 93.33% with a total of 14 coaches and a good percentage of 6, 67% with one coach. In conclusion, this application has the benefits needed by badminton coaches. Keywords: Applications, Badminton Benefits, Physical Conditions